Pde8b haploinsufficiency in mice is associated with modest adrenal defects, impaired steroidogenesis, and male infertility, unaltered by concurrent PKA or Wnt activation. (15th February 2021) - Leal, Leticia Ferro; Szarek, Eva; Berthon, Annabel; Nesterova, Maria; Faucz, Fabio R.; London, Edra; Mercier, Christopher; Abu-Asab, Mones; Starost, Matthew F.; Dye, Louis; Bilinska, Barbara; Kotula-Balak, Malgorzata; et al.
Abstract: PDE8B, PRKAR1A and the Wnt/β-catenin signaling are involved in endocrine disorders. However, how PDEB8B interacts with both Wnt and protein kinase A (PKA) signaling in vivo remains unknown. We created a novel Pde8b knockout mouse line (Pde8b −/− ); Pde8b haploinsufficient (Pde8b +/ − ) mice were then crossed with mice harboring: (1) constitutive beta-catenin activation (Pde8b +/ − ;ΔCat) and (2) Prkar1a haploinsufficieny (Pde8b +/ − ;Prkar1a +/ − ). Adrenals and testes from mice (3-12-mo) were evaluated in addition to plasma corticosterone, aldosterone and Dkk3 concentrations, and the examination of expression of steroidogenesis-, Wnt- and cAMP/PKA-related genes. Pde8b −/− male mice were infertile with down-regulation of the Wnt/β-catenin pathway which did not change significantly in the Pde8b +/ − ;ΔCat mice. Prkar1a haploinsufficiency also did not change the phenotype significantly. In vitro studies showed that PDE8B knockdown upregulated the Wnt pathway and increased proliferation in CTNNB1-mutant cells, whereas it downregulated the Wnt pathway in PRKAR1A-mutant cells. These data support an overall weak, if any, role for PDE8B in adrenocortical tumorigenesis, even when co-altered with Wnt signaling or PKA upregulation; on the other hand, PDE8B appears to play a significant role in male fertility. Highlights: Pde8b haploinsufficiency has a weak effect on adrenal tumorigenesis. Pde8b knockout female mice presented high steroidogenic activity. Pde8b knockout uncovered a significant role in male fertility. Pde8b knockout are mostly related with endocrine disorders rather than tumorigenesis.